Public relations at the crossroads: The need to reclaim core public relations competencies in digital communication - Wolf, Katharina; Archer, C. (Emerald Group Publishing, 2018)
Purpose: Using the theoretical lens of social capital, this paper provides insight into senior public relations (PR) professionals’ views on and attitudes towards digital communication in Singapore and Perth, Western Australia and explores the fundamental question of public relations’ purpose. Design/methodology/approach: Drawing on Bourdieu’s Theory of Practice and in particular his notion of social capital, this exploratory study is based on the critical analysis of 31 semi-structured interviews with senior PR professionals in Singapore and Perth, Western Australia. Findings: PR professionals concur with assumptions made in the extant literature regarding the potential of digital media for public relations, despite broad agreement that the fundamentals of good communication have not changed. At its core public relations is about counselling, relationships and the building of social capital. Hence, digital tools and platforms are typically being referred to as merely an extension of the public relations toolkit. However, as illustrated within the context of influencer engagement, public relations has increasingly adopted advertising-led models and is moved away from its core business of developing strategic relationships and goodwill, hence contributing to the convergence of previously distinct communication functions. Originality/value: This paper is believed to be one of the first to look at the theory of social capital related to public relations within a digital context. Further, it takes a holistic view of public relations professionals’ views on working with digital media in two geographical locations that have been under-represented in scholarly work in the field of public relations. While much of the extant literature has focused on the benefits of social media for public relations, this paper takes a critical look at current challenges, including the rise of social media influencers. The paper contributes to theory relevant to social capital as it looks at the convergence of the professions relevant to digital disruption and argues for public relations claiming its distinctive attributes.